2013
DOI: 10.1007/s13204-013-0212-2
|View full text |Cite
|
Sign up to set email alerts
|

Antigenotoxic effect of green-synthesised silver nanoparticles from Ocimum sanctum leaf extract against cyclophosphamide induced genotoxicity in human lymphocytes—in vitro

Abstract: The present study was aimed to identify the antigenotoxic effect of bio-synthesised silver nanoparticles (SNP) of Ocimum sanctum leaf extract against cyclophosphamide (CP). We tested the antigenotoxic effect of bio-synthesized silver nanoparticles of O. sanctum leaf extract on human lymphocytes against CP by using chromosomal aberration assay (CAA). Silver nanoparticles was first synthesized from fresh leaf extract of O. sanctum and characterised. Their quality was checked by XRD technique and morphology by SE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 18 publications
(16 reference statements)
1
9
0
Order By: Relevance
“…That is why O. sanctum plant has recently drawn an attention for its possible uses in the biogenic synthesis and stabilization of metal nanoparticles [ 1 ],[ 8 ],[ 42 ],[ 43 ]; however, these reported methods suffer from certain shortcomings such as the use of other chemical additives and heating conditions. Hence, development of environmentally more benign, cost-effective, and efficient methodology for the rapid biogenic synthesis of nano-sized metal particles under mild reaction conditions using medicinally significant and edible O. sanctum plant as both metal ion reducing and good capping agent is still warranted.…”
Section: Introductionmentioning
confidence: 99%
“…That is why O. sanctum plant has recently drawn an attention for its possible uses in the biogenic synthesis and stabilization of metal nanoparticles [ 1 ],[ 8 ],[ 42 ],[ 43 ]; however, these reported methods suffer from certain shortcomings such as the use of other chemical additives and heating conditions. Hence, development of environmentally more benign, cost-effective, and efficient methodology for the rapid biogenic synthesis of nano-sized metal particles under mild reaction conditions using medicinally significant and edible O. sanctum plant as both metal ion reducing and good capping agent is still warranted.…”
Section: Introductionmentioning
confidence: 99%
“…Genotoxic and antigenotoxic effects of plant extracts have been evaluated using various genotoxicity tests and experimental organisms (Oyeyemi and Bakare, 2013;Munari et al, 2014;Vijaya et al, 2014). Among vertebrates models, rats (Rattus norvegicus, particularly the albino Wistar and Sprague-Dawley rats) and mice (Mus musculus, particularly the Swiss albino mice) are most important experimental organisms in toxicology and genotoxicology studies, because of an extensive body of knowledge of physiological mechanisms, and cellular and molecular similarity to humans (Vogt, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Foldbjerg et al [25] reported that DNA damage was detected as an increase in bulky DNA adducts by 32P post-labeling in human alveolar cells exposed to 120-150 nm Ag-NPs. On the contrary, no significant genotoxic responses were observed in an Ames test (5 nm) [26], a mouse lymphoma assay (< 100 nm) [27] and an in vivo MN assay (60 nm) [28]. The Ames test is generally used as a first screening method to assess chemical genotoxicity.…”
Section: Resultsmentioning
confidence: 99%